Kecemburuan pada Kaum Homoseksual Pria (Gay) di Jakarta - Prita Aditya; Sarlito Wirawan Sarwono (Fakultas Psikologi Universitas Pancasila, 2009)
Phenomenal incident happened regarding Ryan, a gay who killed and mutilated his victims because of his jealousy. This phenomenal has made the author wants to know about a jealousy among gays, especially in Jakarta. The purpose of this study is to understand about psychodynamic of jealousy, and to give suggestion for intervention strategy development such as counseling for gays. Other purpose is to give description of jealousy of gay in Jakarta. This study used qualitative method. Depth interview and observation we used to collect data. The followings research results are: 1) mainly age of subjects became gay were not in line with theories status the phase of being a gay; 2) all subjects have no father figure or father as negative life-style influence; 3) all subjects are ego dystonic homosexsual, 4) all subjects were stimulated by emotional jealousy; 5) type of jealousy on all sibjects are suspicious jealousy.